Kajian Kehilangan Air pada Saluran Sekunder Balai Gadang Daerah Irigasi (D.I) Koto Tuo Kecamatan Koto Tangah Kota Padang - Abi Sapta Jonesti; Totoh Andayono (MASALIQ, 2026)
Studies on water loss in irrigation networks constitute an important issue in efforts to improve the efficiency of agricultural water distribution, but analyses that specifically examine the components of water loss in secondary canals at the local level remain limited. This study aims to analyze the level of water distribution efficiency and identify the magnitude of water loss in the Balai Gadang Secondary Canal in the Koto Tuo Irrigation Area (D.I.), Koto Tangah Subdistrict, Padang City. This study employed a quantitative approach with a field study design through direct measurements in the irrigation canal. Data were collected using a current meter, canal dimension measuring instruments, and field observations, and were then analyzed through calculations of flow discharge, water loss, and conveyance efficiency. The results showed that water loss in segment 1 was 0.136 m³/s (13.85%) and in segment 2 was 0.064 m³/s (11.5%), with seepage as the dominant factor, while evaporation contributed very little. The water conveyance efficiency was 86% and 88.5%, respectively, thus remaining below the 90% efficiency standard. These findings indicate that the physical condition of the canal and water distribution management are the main factors determining the performance of the irrigation system. This study provides a practical contribution to efforts to improve irrigation efficiency through infrastructure improvement and more optimal water management. The implications of this study are expected to serve as a basis for irrigation management policy-making and to open opportunities for further research based on more comprehensive hydraulic analysis.